Capitalism in the 21st century : through the prism of value - Carchedi, Guglielmo; Roberts, Michael (Economist) (Political economy and development., 2023)
"Contemporary capitalism is always evolving. From digital technologies to cryptocurrencies, current trends in political economy are much discussed, but often little understood. So where can we turn for clarity? As Michael Roberts and Guglielmo Carchedi argue, new trends don't necessarily call for new theory. In Capitalism in the 21st Century, the authors show how Marx's law of value explains numerous issues in our modern world. In both advanced economies and the periphery, value theory provides a piercing analytical framework through which we can approach topics as varied as labour, profitability, automation and AI, the environment, nature and ecology, the role of China, imperialism and the state. This is an ambitious work that will appeal to both heterodox economists and labour movement activists alike, as it demonstrates the ongoing contemporary relevance of Marxist theory to current trends in political economy."--